Bacterial Competition Influences the Ability of Symbiotic Bacteria to Colonize Western Flower Thrips - Andongma, Awawing A.; Whitten, Miranda M. A.; Sol, Ricardo Del; Hitchings, Matthew; Dyson, Paul J. (Frontiers in Microbiology, 2022)
Symbiont mediated RNAi (SMR) is a promising method for precision control of pest insect species such as Western Flower Thrips (WFT). Two species of bacteria are known to be dominant symbiotic bacteria in WFT, namely BFo1 and BFo2 (Bacteria from Frankliniella occidentalis 1 and 2), as we here confirm by analysis of next-generation sequence data derived to obtain a reference WFT genome sequence. Our first demonstration of SMR in WFT used BFo2, related to Pantoea, isolated from a domesticated Dutch thrips population. However, for successful use of SMR as a thrips control measure, these bacteria need to successfully colonize different environmental thrips populations. Here, we describe a UK thrips population that does not harbour BFo2, but does contain BFo1, a species related to Erwinia. Attempts to introduce BFo2 indicate that this bacterium is unable to establish itself in the UK thrips, in contrast to successful colonisation by a strain of BFo1 expressing green fluorescent protein. Fluorescence microscopy indicates that BFo1 occupies similar regions of the thrips posterior midgut and hindgut as BFo2. Bacterial competition assays revealed that a barrier to BFo2 establishing itself in thrips is the identity of the resident BFo1; BFo1 isolated from the UK thrips suppresses growth of BFo2 to a greater extent than BFo1 from the Dutch thrips that is permissive for BFo2 colonisation. The ability of the latter strain of BFo1 to colonize the UK thrips is also likely attributable to its ability to out-compete the resident BFo1. Lastly, we observed that UK thrips pre-exposed to the Dutch BFo1 could then be successfully colonized by BFo2. These results indicate, for the first time, that microbial competition and strain differences can have a large influence on how symbiotic bacteria can colonize different populations of an insect species.